HIGH EFFICIENT 3.6GHz 4 – ELEMENT CPW FED MIMO ANTENNA USING U – SHAPED OPEN SPIRAL SLOTS FOR 5G MOBILE COMMUNICATIONS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This paper presents the investigation on different substrates that can be used indesigning of microstrip monopole antenna such as FR – 4, Arlon 250 ™, Rogers RT / Duroid5880 ™, Teflon and Rogers RO4350 to operate at 3.6GHz frequency. Main aim of this paperis to propose 4 x 4 Multiple-Input Multiple-Output (MIMO) antenna with coplanarwaveguide (CPW) fed technique operating at 3.3 – 3.8GHz for advanced 5G mobileapplications. With the help of orthogonal mode arrangement, isolation between MIMOantennas is better than 12dB and achieved radiation efficiency of 97 – 98%. Proposedantenna achieves 550MHz impedance bandwidth at S11< -10dB over operating bandwidthfrom 3.33 GHz to 3.88 GHz and its peak gain value is 4.90dB. The design is suitable for fifthgeneration mobile communications exhibited by MIMO antenna performance parametersEnvelope correlation coefficient (ECC) < 0.01, diversity gain (DG) ~ 10dB, total activereflection coefficient (TARC)